The Perspectives of Family Specialists on the Socio-Cultural Challenges of Family Therapy Interventions in Iran: A Qualitative Study - Ordukhani, Maryam; Kachooei, Mohsen; Keshmiri, Morteza (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to explore the socio-cultural challenges of family therapy. This applied research utilized a qualitative phenomenological approach. Methods: The study population consisted of specialists in various fields of couples and family therapy in Tehran province during the years 2022-2023, who met the inclusion criteria for the study. The inclusion criteria were psychologists or counselors with a Master’s or Doctoral degree who had at least five years of experience in one of the family-related fields and were willing to collaborate in the research. A purposive, snowball sampling method was used, continuing until data saturation was reached, with a final selection of 15 specialists. Semi-structured interviews were used for data collection, and the data were analyzed using an inductive thematic analysis approach. Findings: The findings revealed 24 initial concepts, 5 sub-themes, and 2 main themes as the socio-cultural challenges and factors that perpetuate these challenges. Ineffective application of existing family therapy theories in response to societal changes, social harms affecting family systems over time, and socio-cultural-economic damages were among the sub-themes of challenges. Differences in opinions regarding the strengthening of theory-building and the approach to localizing interventions without relying on existing theories were identified as factors that sustain these challenges. Conclusion: This study offers a new perspective on the impact of societal context on the effective or ineffective implementation of interventions based on non-native theories, providing an alternative approach to examining the issues of cultural insularity in interventions, beyond considerations of religion and written documents in research.